The Relevance of Islamic Education with Indonesian Culture - Nia Samania; Harun, Makmur Haji; Hosaini (Rumah Riset Publisher, 2023)
Islamic education cannot be separated from cultural values. Especially in Indonesia, an archipelagic country consisting of more than 17,000 islands and inhabited by around 255 million people. The number indicates that cultural, ethnic, religious and linguistic diversity must be found in Indonesia. This diversity is a characteristic as well as a valuable asset that must be cared for, fostered, protected and preserved. One attempt to maintain culture can be pursued through education. The relationship between Islamic education and Indonesian culture is like a currency coin that must synergize and strengthen each other, because education is actually a cultural process. The importance of Islamic religious and cultural education is contained in the Law on the National Education System (No. 20/2003) which states that education is a conscious and planned effort to create a learning atmosphere and process so that students actively develop their potential, to have religious spiritual strength, self-control, personality, intelligence, noble character, and skills needed by themselves, society, nation and state. This journal will discuss the relevance between Islamic education and culture. The research was conducted using the library research method. The results of the study show that Islamic religious education and Indonesian culture have a very significant and inseparable relevance. Islamic Religious Education must be able to lay a moral, ethical, and spiritual foundation for the development of Indonesia, which has a diverse cultural background.